Policy to reduce greenhouse gas emissions: Is agricultural methane a special case? - Lynch, J; Garnett, T (Wiley, 2021)
Climate change mitigation will require significant efforts from all emitting sectors, including agriculture. However, agricultural emission reduction measures raise specific concerns, both in respect of their distinct climate outcomes and how their implementation might support or frustrate wider objectives. We highlight some special characteristics regarding agricultural methane emissions. As methane is a relatively short-lived gas, we do not have the same strong physical requirement to completely eliminate net methane emissions as we do for carbon dioxide. An appreciation of the distinct nature and impacts of carbon dioxide and methane can bring nuance to discussions; especially around what different sectors must be expected to achieve, and thus help avoid negative trade-offs that might result from heavy-handed policy interventions. Nevertheless, significant and rapid methane emission reductions do remain important in realistically achieving our overall climate objectives. A number of technical measures to reduce ruminant methane are highlighted, but are not without their own challenges; and we are unlikely to meet climate or other environmental targets without systemic changes to the total food system, including overall consumption patterns. The appropriate policy tools to achieve these changes are emerging as a key, but contested, concern in Europe and beyond, making it vital we work through these arguments in a transparent manner.